Pengelolaan Evaluasi Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Hasil Belajar (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the management of evaluation in Islamic Religious Education (IRE) learning to improve students’ learning outcomes. The study is motivated by the prevailing tendency of evaluation practices that predominantly focus on cognitive aspects and fail to reflect a comprehensive assessment of affective and psychomotor domains. This research employs a qualitative approach using a literature review method by examining and synthesizing various relevant academic sources. The data were analyzed through content analysis to identify conceptual patterns and trends in IRE evaluation practices. The findings indicate that evaluation in IRE should be holistic and integrative, encompassing balanced assessments of knowledge, attitudes, and religious skills. However, in practice, several issues persist, including the misalignment between learning objectives and evaluation instruments, limited teacher competence, and the dominance of administrative orientation. The development of holistic evaluation instruments emerges as a strategic solution to address these challenges through the application of authentic, continuous, and contextual assessment techniques. Effective management of evaluation not only enhances academic achievement but also fosters the development of students’ religious character in a substantive manner. Keywords: learning evaluation, Islamic religious education, learning outcomes, holistic assessment, evaluation management